Phase II multicenter trial combining nivolumab and radiosurgery for NSCLC and RCC brain metastases. Issue 1 (1st March 2023) - Wong, Philip; Masucci, Laura; Florescu, Marie; Plourde, Marc-Emile; Panet-Raymond, Valerie; Pavic, Michel; Owen, Scott; Masson-Coté, Laurence; Ménard, Cynthia; Routy, Bertrand; Tehfe, Mustapha; Nelson, Kristoff; et al.
Abstract: Background: Anti-PD-1 has activity in brain metastases (BM). This phase II open labeled non-randomized single arm trial examined the safety and efficacy of combining nivolumab with radiosurgery (SRS) in the treatment of patients with BM from non-small cell lung cancer (NSCLC) and renal cell carcinoma (RCC). Methods: This was a multicenter trial (NCT02978404) in which patients diagnosed with NSCLC or RCC, having ≤ 10 cc of un-irradiated BM and no prior immunotherapy were eligible. Nivolumab (240 mg or 480 mg IV) was administered for up to 2 years until progression. SRS (15–21 Gy) to all un-irradiated BM was delivered within 14 days after the first dose of nivolumab. The primary endpoint was intracranial progression free survival (iPFS). Results: Twenty-six patients (22 NSCLC and 4 RCC) were enrolled between August 2017 and January 2020. A median of 3 (1–9) BM were treated with SRS. Median follow-up was 16.0 months (0.43–25.9 months). Two patients developed nivolumab and SRS related grade 3 fatigue. One-year iPFS and OS were 45.2% (95% CI 29.3–69.6%) and 61.3% (95% CI 45.1–83.3%), respectively. Overall response (partial or complete) of SRS treated BM was attained in 14 out of the 20 patients with ≥1 evaluable follow-up MRI. Mean FACT-Br total scores were 90.2 at baseline and improved to 146.2 within 2–4 months ( P = .0007). Conclusions: The adverse event profile and FACT-Br assessments suggested that SRS during nivolumab was well tolerated. Upfront SRS with the initiation of anti-PD-1 prolonged the 1-year iPFS and achieved high intracranial control. This combined approach merits validation randomized studies.